Tudo o que o seu mestre mandar: a figuração do narrador e do leitor nos texto interativos - Alves, Maria Angélica (1997)
Analyse the structure of the young reader, one-player interactive books. The playing elements in the construction of the narrative as well as the specific configuration of the literary text itself are major topics of this study. The concept of interactivity and its contradictions within the narrative, helps discussing the role the reader plays coauthoring the work of fiction. The reader becomes a game player, being part of the plot, choosing from the options presented by an oniscient narrator who is basically the adventure's scrip-writer. Overcoming the linear structure of the conventional fiction, the "play book" devises new perspectives for the relationship between the reader and the book. A final consideration deals with the function and importance of fiction and the roles of readers and of reading in contemporary society while highligting the new ways and usages of books in the future.